Physical activity and quality of life in prostate and breast cancer patients: A comparative study - Ribovski M.* (2018)
© 2018 Universidade Estadual de Maringa. All rights reserved.The objective of this study was to compare the physical activity (PA) and quality of life (QL) of patients with prostate cancer (PC) and breast cancer (BC) undergoing clinical treatment and after treatment. Cross-sectional study with 148 patients (44 men and 104 women), mean age of 58.77±10.53 years old, data collect with questionnaire, containing: general information, economic status (IBGE), PA (IPAQ – short version) and QL (EORTC QLQ-C30). About the PA, 73.1% of the patients with BC were insufficiently active and also 63,6% of the patients with PC, with no difference between both (p=0,251). The time total of PA practice was 32,5 min/day for the BC patients and 39,0 min/day for the PC patients. PC patients that practiced more PA reported less insomnia (p=0,021). More, they presented better functional scale (75,4±20,0) as the symptomatic scale (19,1±17,8) of QL, highlighting worse scores for the BC patients on the variables of fatigue (39,4±36,3; p=0.027), nauseas/vomits (12,9±23,4; p=0.048) and financial difficulties (30,7±39,0; p=0.034). We conclude that there was no difference between groups related to PA, however, the PC patients presented better scores in the functional and symptomatic scales when comparing to BC patients.